83 Assessing depression on admission to hospice: an audit. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Wood, Felicity; Lowe, Emma
Abstract : Background: Depression is prevalent but often undiagnosed and undertreated in hospice settings. The aim of this audit was to establish how well depression is assessed and managed on admission to hospice and during the course of admission. Method: All admissions to Wakefield hospice between April and June 2018 were examined. The electronic GP notes were accessed to determine if an established diagnosis of depression was recorded. Written hospice notes were then reviewed. Demographic information was collected as well as whether depression was assessed on admission, and whether it was rated, as per the medical admission proforma. If mood was recorded as low, it was noted whether a plan was in place regarding this. The medical entries during admission were also read to see if depression was assessed during the course of admission. Results: There were 87 patients admitted to the hospice during the 3 month period. Data was available on 61 of those. Less than a third of depression diagnoses documented by GP were noted on admission. In 48% of cases depression was assessed on admission. When recorded as being low in mood, there was rarely a plan specified in managing this. In only 6% of all notes was a rating score recorded for depression. This is part of the admission proforma. In 10% of cases, there was some review of mood made during the course of admission. Conclusion: Despite depression being prevalent in a hospice setting, an assessment of this was recorded in less than half of cases on admission. Mood was infrequently documented during the course of admission. When depression was noted, there was not often a plan documented for managing or reviewing this. The plan is to update the admission proforma, educate staff on depression screening and re-audit in 6 months time.